Visual Aesthetics “Djarum Black Motodify” Branding in Urban Lifestyle a Case Study (Visual Methodology Approach) - Andreas Slamet Widodo (Graduate School of Institut Seni Indonesia Yogyakarta, 2017)
This development of image brand (branding) conducted by Djarum corporate, its Djarum Black was held with the visual communication approach who made urban lifestyle. This was embodied in the form of advertising and the activity of the urban lifestyle, one of them are “Djarum Black Motodify” event. Based on these phenomena, then the researcher focused on visual aesthetic branding Djarum Black (media and event) which conceived Djarum Black urban lifestyle are aimed for consumers. This research using visual methodology approach to give a description and explain the structure of matter visual code or associated mark with the symbol of contemporary culture. A critical approach use visual methodology, which means that visual to be considered placed in the community, and how visual it will have an impact on a culture. This is the incident happened in the daily, because it often many matters relating to the media visual found that we shall not see a phenomenon that occurs well. When a strategy of promotion through the visual and event have overcome reality and duplicate themselves quickly and sporadic, then aesthetics has captured the world and eliminate reality. A consequence, various “life” reduced into symbols codification and abstraction of the promotion strategy.